ANALISIS PERPUTARAN MODAL KERJA PADA PT. MAYORA INDAH TBK - AMRIN, SAIFUL; MUNIARTY, PUJI; APRIANTI, KARTIN (GANEC SWARA, 2024)
The aim of this research is to analyze PT Mayora Indah, Tbk on the working capital turnover ratio. This research uses a descriptive type with a quantitative approach. This research uses a purposive sampling technique and uses profit and loss financial reports consisting of sales reports, initial working capital and final working capital from 2013 to 2022 as the sample. First, the latest financial report data, and second, data for a ten-year period, specifically 2013–2022, is used as a standard. The analysis used is SPSS version 22 software which includes Statistical Analysis and One Sample Test. This research shows that the working capital turnover ratio is six times lower than expected.